Effects of senolytic drugs on human mesenchymal stromal cells - Clara Grezella; Eduardo Fernandez-Rebollo; Julia Franzen; Mónica Sofia Ventura Ferreira; Fabian Beier; Wolfgang Wagner (Stem Cell Research & Therapy, 2018)
Abstract Background Senolytic drugs are thought to target senescent cells and might thereby rejuvenate tissues. In fact, such compounds were suggested to increase health and lifespan in various murine aging models. So far, effects of senolytic drugs have not been analysed during replicative senescence of human mesenchymal stromal cells (MSCs). Methods In this study, we tested four potentially senolytic drugs: ABT-263 (navitoclax), quercetin, nicotinamide riboside, and danazol. The effects of these compounds were analysed during long-term expansion of MSCs, until replicative senescence. Furthermore, we determined the effect on molecular markers for replicative senescence, such as senescence-associated beta-galactosidase staining (SA-β-gal), telomere attrition, and senescence-associated DNA methylation changes. Results Co-culture experiments of fluorescently labelled early and late passages revealed that particularly ABT-263 had a significant but moderate senolytic effect. This was in line with reduced SA-β-gal staining in senescent MSCs upon treatment with ABT-263. However, none of the drugs had significant effects on the maximum number of population doublings, telomere length, or epigenetic senescence predictions. Conclusions Of the four tested drugs, only ABT-263 revealed a senolytic effect in human MSCs—and even treatment with this compound did not rejuvenate MSCs with regard to telomere length or epigenetic senescence signature. It will be important to identify more potent senolytic drugs to meet the high hopes for regenerative medicine.